Attenuation of strong earthquake ground motion – II: Dependence on geology along the wave paths from the Burmese subduction zone to northeastern India. Issue 112 (September 2018) - Gupta, I.D.; Trifunac, M.D.
Abstract: This paper presents another example of event-specific, region-specific attenuation equations for strong earthquake ground motion through essentially the same geological region defined by geometrically constrained ray paths. The current study describes strong motion wave attenuation from deep earthquakes in the Burmese subduction zone, as recorded by strong motion accelerographs in northeastern India. The accompanying empirical scaling equations to determine the Fourier and pseudo-relative velocity (PSV) spectra for the same events are also presented. To demonstrate the validity of the long-period extension of the above spectra, independent estimates of peak ground displacement from recorded accelerograms and estimates of the seismic moment from distant recordings of earthquakes are shown to be in good agreement with the extended spectral amplitudes. The validity of a short-period extension has been tested by comparing the values of pseudo acceleration spectral amplitudes at short periods with the recorded peak ground accelerations. Presented Fourier and PSV spectra can thus be considered to provide a sound basis for macro- and micro-zoning specific to the highly seismic regions of northeastern India. Highlights: Frequency dependent attenuation of strong motion from Burmese earthquakes. Scaling equations for Fourier and PSV Spectra from Burmese earthquakes. Scaling strong motion amplitudes in northeast India up to distances of 570 km. Tests of empirical Fourier and PSV spectra at long periods in terms of seismic moment.